The Effectiveness of Using Running Dictation Technique to Improve Students Writing Skill at SMAN 8 Lubuklinggau - Ningsih, Ratih; Ramasari, Maria; Yulfi, Yulfi (Edu-Ling: Journal of English Education and Linguistics, 2024)
This research was aimed to prove that it was significantly effective to teach writing skill by using running dictation technique of hortatory exposition text to the eleventh grade students of SMAN 8 Lubuklinggau. This research used a pre-experimental design with one group pre-test and post-test. The population of this research was the eleventh grade students of SMAN 8 Lubuklinggau that consisted of 123 students. The sampling technique used was cluster random sampling with the method of paper roll and the sample selected was XI IPA 2 class consisted 25 students. The data for this research was collected by using a written test. The result of this research could be proved by the significant difference between the mean score in the pre-test and post-test. The students mean score in the pre-test was 61.28 and in the post test was 75.44. The t-obtained was 12.367, it was higher than 1.71387 as the critical value in t-table. Finally, the researcher found that “The effectiveness of Using Running Dictation Technique to Improve Students Writing Skill at SMAN 8 Lubuklinggau” was effective. Therefore, it was clearly stated that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Keywords: Hortatory Exposition Text, Running Dictation, Writing Skill